GABUNGAN PERKARA TINDAK PIDANA KORUPSI DAN TINDAK PIDANA PENCUCIAN UANG (STUDI PUTUSAN MAHKAMAH AGUNG NO. 1294 K/PID.SUS/2015) - Oki Yudhatama; Alvi Syahrin; Bismar Nasution; Mahmud Mulyadi (USU LAW JOURNAL, 2018)
ABSTRACT Supreme Court Decision No. 1294 K/PID.SUS/2015 on corruption and money laundering, the convicted person named Mohammad Bahalwan was sentenced to imprisonment for corruption, namely 14 years imprisonment and a fine of Rp. 1,000,000,000.00 (one billion rupiah) provided that if the fine is not paid, it is replaced with imprisonment for 8 (eight) months and punishes the defendant to pay the replacement Rp. 337,429,393,537,00 (three hundred thirty seven billion four hundred twenty nine million three hundred ninety three thousand five hundred thirty seven rupiah) where the payment deadline is 1 (one) month after the decision of permanent legal force. However, if not paid will be replaced with imprisonment for 5 (five) years. The imposition of sanctions is due to the convict proven to violate Article 2 paragraph (1) of Law no. 31 Year 1999 on the Eradication of Corruption.   Keywords: Corruption, Money Laundering and Evidence